Hi all, I understand the basic concept of undetermined coefficients, but am a little lost when g(t) in the equation yll+p(t)yl+q(t)y=g(t) is a product of two functions. The specific problem I'm working on is as follows: yll-2yl-3y=-3te-t When I solve for the homogeneous set of solutions I get roots 3 and -1 (r2-2r-3)=0 (r-3)(r+1)=0 Therefore, I have y(t)=c1e-t+c2e3t Now, if g(t) were just equal to -3e-t I would just set Y(t)=Ae-t and use Y(t) to solve for the particular solution. However, because g(t) is the product of two equations, I am not sure how to proceed at this point. Someone suggested that I use the homogeneous set of solutions as my Y(t), solve for Yl(t) and Yll(t) and plug those back into my original equation. Is this the correct way to approach this problem? And if so, how exactly am I supposed to do this? Thanks for any help!!